Strategi Promosi Objek Wisata Alam Situ Gede Kota Tasikmalaya - Ajeng Puspita Priantana; Edi Santoso (Jurnal Komunikasi Global, 2019)
Situ Gede Tourist Site Tasikmalaya has a lot of potential as a tourist attraction, but natural it was neglected and had only a few visitors until the local Tourism Office has managed and promoted the tourist site. This study aimed to analyse the tourism promotion strategy of Situ Gede by the local Tourism Office using the concept of the promotion mix. This research is qualitative research in which data were collected through interviews with four key informants from the local Tourism Office. Informants were selected using purposive sampling technique. The results of the study show that the marketing strategy carried out by the Tourism Office including advertising, direct marketing, sales promotion, personal sales, interactive marketing, public relations, has succeeded in increasing the number of tourists.